VD_FINDINFO HC / 2011 / 312 vom 17. Mai 2011 - VD Tribunal cantonal (2011)
EFFET DE REPRÉSENTATION, LÉGITIMATION ACTIVE ET PASSIVE, PROCÉDÉ TÉMÉRAIRE | 712l CC, 32 CO, 336b CO, 343 al. 3 CO, 10 LJT, 42 LJT, 46 LJT